A Low Cost Thermal Imaging System for Medical Diagnostic Applications - Jayalatsumi, U; Feza Naaz, A; Sravani, Kodavaluru; Anusha, A; Vasavi, Alla (International Journal of Engineering and Technology, 2018)
This paper presents a low cost thermal imaging system for medical diagnostic applications. Available systems are expensive and are mostly meant for industrial applications. In this paper the existing system which is a basic system consisting of thermopile based sensor which produces thermal array is replaced with a â€œThermal Imaging Cameraâ€ for medical diagnosis applications. The thermal camera scans the entire body of the individual to diagnose the diseases ie, infrared radiations from the human body part and then converts them to electronic signal. If there is any lump or any other unusual change inside the body, then the body temperature at that particular part will alone be high or low which indicates the â€œHypoâ€ or â€œHyperâ€ condition of the disease. Scene captured by the thermal camera is represented as a matrix. Each element of matrix represents a temperature value. Temperature values are divided into different ranges and each range is represented by an RGB value by the Raspberry Pi. Â Based on this thermal camera image we can detect the exact location in individual body part and further for that part alone we can take test and detect what kind of disease the individual is suffering. This system can be used in wide applications in the field of medicine such as detection of breast cancer, fever screening, thyroid disease detection, early detection of risk for diabetic peripheral neuropathy, Reynaudâ€™s phenomenon, orthopedics etc.Â Â